The Magnitude and Causes of Job Polarization: A Local Labor Market Approach - Wolfgang Dauth (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper examines job polarization at the level of local labor markets in Germany over a 30-year period. The major explanation of job polarization is skill biased technological change (SBTC): new technologies are complementary to high paying jobs but substitute workers in routine manual jobs in the middle of the wage distribution, who relocate to low paying service jobs. Several recent papers use regional data to analyze if there is a relation between routine labor and the growth of service jobs, but provide no evidence if the region's labor markets are actually polarized. I close this gap by first introducing an intuitive and simple index to measure the magnitude of job polarization. Then I use comprehensive data on all German employees subject to social security to calculate this index for 204 local labor markets (LLM) in Western Germany between 1980 and 2010. I find that there are substantial disparities if and how strongly LLM are polarized. About one half of all German LLM exhibit significant job polarization, while some others are even inversely polarized. In an econometric analysis, I use this measure to examine the relation between the regional economic structure in the beginning of the period and job polarization. The main finding is that the explanation of SBTC does not apply to all regions to the same extend. Urban regions with many export oriented manufacturing industries in 1980 are most likely to polarize, while SBTC does not seem to have led to polarization in rural regions specialized in traditional manufacturing.
Keywords: J31; J24; R23; 330